2006
DOI: 10.1111/j.1463-1318.2006.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Convalescence after colonic surgery with fast‐track vs conventional care

Abstract: A fast-track rehabillitation programme led to a shorter hospital stay, less fatigue and earlier resumption of normal activities, without the increased need for support after discharge compared with conventionally treated patients after uncomplicated colonic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 10 publications
2
81
0
8
Order By: Relevance
“…The findings underpin the importance of early surgical rehabilitation embedded in the surgical peri-and post-operative fast-track concept [13]. Within colorectal surgery, research in evidence-based fast-track regimes has revealed well documented effects internationally with regard to rapid recovery and reduced hospitalization [14][15][16]. The fast-track concept has gained wide acceptance internationally and is seen today as a standardized multimodal surgical rehabilitation program [17].…”
Section: 'Fast-track' -A Multimodal Rehabilitation Programmentioning
confidence: 99%
“…The findings underpin the importance of early surgical rehabilitation embedded in the surgical peri-and post-operative fast-track concept [13]. Within colorectal surgery, research in evidence-based fast-track regimes has revealed well documented effects internationally with regard to rapid recovery and reduced hospitalization [14][15][16]. The fast-track concept has gained wide acceptance internationally and is seen today as a standardized multimodal surgical rehabilitation program [17].…”
Section: 'Fast-track' -A Multimodal Rehabilitation Programmentioning
confidence: 99%
“…Fatigue is pronounced after major abdominal surgery, probably because of inflammatory response. 15,20,56 Despite a multimodal analgesia regime, including thoracic epidural with local anesthetics and oral NSAIDs, a large proportion of patients experienced moderate to severe pain in the abdominal area during mobilization. Thus, 13%-20% of the patients reported pain as the main barrier to independent mobilization on PODs 2-7.…”
Section: Barriers To Independent Mobilizationmentioning
confidence: 99%
“…8,10,12 Early mobilization and exercise are known to play important roles in postoperative care following abdominal surgery and are associated with less postoperative reduction of fitness and fewer postoperative complications in patients undergoing elective surgery. 9,[15][16][17][18][19][20] There are, to our knowledge, no published data on postoperative physical performance, level of 24-hour physical activity, or barriers to independent mobilization within the first week following AHA surgery. Such findings are crucial when organizing strategies for enhanced recovery programs after AHA surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed reduction in hospital stay, reducing ileus and cardiopulmonary complications. 10,[13][14][15][16][17][18][19][20][21][22][23] Also in rectal cancer surgery the peri-operative "fast-track" multimodal rehabilitation program is effective and safe. 24,25 Randomised controlled trials (RCT) have showed the same results, 19,20,22,23,[27][28][29] though Behrns patients were discharged on liquid diets.…”
Section: Erasmentioning
confidence: 99%